Penggunaan Media Benda Konkret Guna Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas II Madrasah Ibtidaiyah Nahdlatuth-Thullab - Chlara Cristiana Clara; Diliza Afrila; Dian Anggraeni Maharbid (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2023)
Good learning is learning that requires teacher activity, student activity, and innovative learning models so as to increase the effectiveness of learning. At the school where the researcher is located, the teacher often applies the lecture method, especially in learning Mathematics, the teacher only explains and then instructs students to work on practice questions. This causes boredom, is not conducive to learning and reduces student learning outcomes. The purpose of this study was to increase teacher activity, student activity, and student learning outcomes of Madrasah Ibtidaiyah Nahdlatuth-Thullab II class in learning mathematics after using a concrete environment. This type of research is classroompaction research carried outpin 4 stages, namely planning, pimplementing, observing, preflecting. The subjects in this study were 2nd gradepstudents, totaling 35 students. This research was conducted at Madrasah Ibtidaiyah Nahdlatuth-Thullab. And research tools in thepform of observationpsheets andptests. The analysis of this research waspcarried out descriptively. The results showed an increasepin learning outcomes. This can be seen from the activities of teachers and students who are accustomed to using concrete media objects. Besides that, it can also be seen from the results of student learning through tests which are always increasing. In cycle I, student learning outcomes reached 51.43%, while in cycle II it increased to 97.14%. Based on the research data, it can be concludedpthat the use of concrete objects can increase the activity of teachers and students, as well as the results of learning mathematics for second graders of Madrasah Ibtidaiyah Nahdlatuth-Thullab.